2001
DOI: 10.1046/j.1469-8137.2001.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal vs saprotrophic status of fungi: the isotopic evidence

Abstract: Summary• Relative abundances of carbon and nitrogen isotopes in fungal sporocarps are useful in assessing mycorrhizal or saprotrophic status, and might provide insights into the evolutionary history of these traits.• Sporocarps of known mycorrhizal or saprotrophic genera were collected at Woods Creek, OR, USA, and isotopically compared with foliage, litter, soils and wood collected from the same site. Possible trophic strategies were then isotopically assessed in archived specimens of the Pezizales of known mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
130
5
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 28 publications
15
130
5
1
Order By: Relevance
“…As reported by several authors (Gebauer and Taylor, 1999;Henn and Chapela, 2001;Hobbie et al, 1999Hobbie et al, , 2001Högberg, 1997;Kohzu et al, 1999;Taylor et al, 2003, Trudell et al, 2004Zeller et al, 2007), δ 13 C values differed between sporophores of saprotrophic and ectomycorrhizal fungi. Sporophores of the two saprotrophic fungi from the Châteauvert site showed a 13 C enrichment compared to their substrates.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As reported by several authors (Gebauer and Taylor, 1999;Henn and Chapela, 2001;Hobbie et al, 1999Hobbie et al, , 2001Högberg, 1997;Kohzu et al, 1999;Taylor et al, 2003, Trudell et al, 2004Zeller et al, 2007), δ 13 C values differed between sporophores of saprotrophic and ectomycorrhizal fungi. Sporophores of the two saprotrophic fungi from the Châteauvert site showed a 13 C enrichment compared to their substrates.…”
Section: Discussionmentioning
confidence: 68%
“…The three Tuber species displayed a high δ 15 N value (9.3 to 10.4% ). Hobbie et al, (2001) also found for T. gibbosum, a North American truffle, high δ 15 N values (12.0 to 16.6% ). In the Châteauvert site, the amplitude of δ 15 N variation among ectomycorrhizal sporophores was similar to the amplitude observed in the Breuil forest (-1.0% to 10.2% ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Stark et al (2009) speculated morels were associated with orchids, based on evidence obtained through PCR-amplification directly from root-extracted DNA and cloning of the PCR products. Hobbie et al (2001) and Li et al (2013) assessed the trophic status of morels by examining the relative abundance of stable isotopes. Hobbie et al (2001) suggested that morels were largely saprophytic, but Li et al (2013) suggested that morels with black pilei were saprophytic and those with yellow pilei were mycorrhizal.…”
Section: Species Distribution and Ecological Diversity Of Morchellamentioning
confidence: 99%
“…Hobbie et al (2001) and Li et al (2013) assessed the trophic status of morels by examining the relative abundance of stable isotopes. Hobbie et al (2001) suggested that morels were largely saprophytic, but Li et al (2013) suggested that morels with black pilei were saprophytic and those with yellow pilei were mycorrhizal. Baynes et al (2012) detected Morchella as an endophyte in the aboveground stem tissue of cheatgrass and reported that M. sextelata M. Kuo and M. snyderi M. Kuo & Methven could infect cheatgrass roots.…”
Section: Species Distribution and Ecological Diversity Of Morchellamentioning
confidence: 99%